2007
DOI: 10.1007/s11104-007-9281-x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic carbon affects soil microbial activity and nitrogen dynamics in a Mexican tropical deciduous forest

Abstract: Seasonal variation of dissolved organic C (DOC) and its effects on microbial activity and N dynamics were studied during two consecutive years in soils with different organic C concentrations (hilltop and hillslope) in a tropical deciduous forest of Mexico. We found that DOC concentrations were higher at the hilltop than at the hillslope soils, and in both soils generally decreased from the dry to the rainy season during the two study years. Microbial biomass and potential C mineralization rates, as well as di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 48 publications
5
45
0
8
Order By: Relevance
“…The greater stability of aggregates and total porosity at the upper position of the hillslope could be due to the organic carbon content, although there were no significant differences in the organic carbon content in both hillslope positions (Table 4). Montaño et al (2007) found that organic carbon concentrations were higher at the hilltop than at the hillslope soils, which is in line with a higher organic material accumulation.…”
Section: Effect Of Slope Positionsupporting
confidence: 59%
See 1 more Smart Citation
“…The greater stability of aggregates and total porosity at the upper position of the hillslope could be due to the organic carbon content, although there were no significant differences in the organic carbon content in both hillslope positions (Table 4). Montaño et al (2007) found that organic carbon concentrations were higher at the hilltop than at the hillslope soils, which is in line with a higher organic material accumulation.…”
Section: Effect Of Slope Positionsupporting
confidence: 59%
“…García-Oliva et al (2003) There are different studies disclosing that in dry season, greater contents of total carbon are acquired, decreasing of this property from dry to wet season suggests a rapid decomposition and mineralization of litter-derived organic materials during the wet season (Montaño et al, 2007;Yamashita et al, 2011). These soil processes could be positively influencing the stabilization of soil aggregates.…”
Section: Son (Tabla 3) Soil Samples Collected In Rainy Seasonmentioning
confidence: 99%
“…The enhanced supply of heat and water in the summer might have affected WSOC and WSON concentrations through changing the soil microbial activities (Michalzik . Previous research found that lower WSOC in the rainy season was accompanied by lower microbial biomass in tropical rainforests (Garcı´a-Oliva et al 2003;Montan˜o et al 2007). Because WSOC could be both a product of and substrate for soil microbes, the lower WSOC in the rainy season could have been caused by the extensive consumption of WSOC at the early-rainy season or the low microbial production of WSOC (Montan˜o et al 2007).…”
Section: Discussion Seasonal Patterns Of Wsoc Wson and Wsoc: Wson Ramentioning
confidence: 92%
“…Arrows represent hypothesized direction of change in pool or process under N deposition. (Montano et al, 2007), N, and P (Galicia and Garcia-Oliva, 2004) are dependent upon season and the intensity of plant-microbe competition.…”
Section: Figure 1 | Conceptual Model Of How Nitrogen Addition Affectsmentioning
confidence: 99%